The hard way : a Jack Reacher novel - Child, Lee (New York : Delacorte Press, 2006)
On the trail of a vicious kidnapper, Reacher is learning the chilling secrets of his employer$1 (Bs past$1! =(Band of a horrific drama in the heart of a nasty little war. He$1 (Bs beginning to realize that Edward Lane is hiding something. Something dirty. Something big. But Reacher also knows this: he$1 (Bs already in way too deep to stop now.s
Keywords: Ex-police officers -- Fiction; Mercenary troops -- Fiction; Suspense fiction